Vitamin A Status Is More Commonly Associated With Symptoms and Neurodevelopment in Boys With Autism Spectrum Disorders—A Multicenter Study in China - Yang, Ting; Chen, Li; Dai, Ying; Jia, Feiyong; Hao, Yan; Li, Ling; Zhang, Jie; Wu, Lijie; Ke, Xiaoyan; Yi, Mingji; Hong, Qi; Chen, Jinjin; et al. (Frontiers in Nutrition, 2022)
Background: Autism spectrum disorder (ASD) is a neurodevelopmental disorder, and show a striking male bias in prevalence. Vitamin A (VA) is essential for brain development, and abnormalities in its metabolite retinoic acid are associated with the pathophysiology of ASD. This national multicenter study was conducted to investigate the relationship between serum VA level and core symptoms in ASD children and whether there are still sex differences. Method: A total of 1300 children with ASD and 1252 typically-developing (TD) controls aged 2-7 years old from 13 cities in China were enrolled in this study. The symptoms of children with ASD were evaluated by the Autism Behavior Checklist (ABC), Social Responsiveness Scale (SRS), and Childhood autism rating scale (CARS). The neurodevelopmental level of the children was evaluated with the revised Children Neuropsychological and Behavior Scale (CNBS-R2016). The serum level of VA was measured by high-performance liquid chromatography (HPLC). Results: The serum VA level in children with ASD was significantly lower than that in TD children, especially in boys with ASD. Furthermore, VA levels in male children with ASD were lower than those in female children with ASD. In addition, we found that serum VA level was negatively correlated the SRS, CARS and communication warming behavior of CBNS-R2016 scores in boys with ASD. In terms of developmental quotients, serum VA level was positively associated with the general quotient, language quotient, gross motor quotient and personal-social quotient of boys with ASD, but no difference was found in girls with ASD. Conclusions: ASD children, especially boys, have lower serum VA levels than TD children. Moreover, serum VA status is more commonly associated with clinical symptoms and neurodevelopment in boys with ASD.